Hubungan Pencemaran Lingkungan Laut Terhadap Ekologi Pesisir Pantai Kenjeran Surabaya - Febriani, Suci (PEDAGO BIOLOGI, 2023)
Garbage in the coastal settlements of Kenjeran Surabaya is a habit that can have an impact on environmental pollution in the area, so the purpose of this study was to determine the waste waste and the composition of waste in the coastal settlements of Kenjeran Surabaya. The method used is a literature study with a qualitative approach, waste and waste composition can be used for management planning in Kenjeran coastal settlements, Surabaya. The condition of the environment and the coastal ecosystem of Kenjeran which had been damaged at that time caused the coastal scenery to become less beautiful, as a tourist place it resulted in Kejeran coastal tourism becoming less desirable. The current government has also taken over to manage and revive tourism on the Kenjeran coast and also further enhance the beauty that has been provided by nature, then reprocessed this policy so that it can help people in the Kenjeran coastal area. to revive the current economy.                                    Keywords: ecology, pollution, tourism